2011
DOI: 10.1242/jeb.046607
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing a set of olfactory sensory neurons responding to a bile salt

Abstract: SUMMARYIn the present study, we exposed the olfactory epithelia of crucian carp, Carassius carassius, and brown trout, Salmo trutta, to dextran coupled with Alexa dyes together with odorants. Dye uptake was severely reduced after pre-exposure to nocodazole, an inhibitor of microtubule polymerization that impairs endocytosis, supporting the hypothesis that odour-activated olfactory receptor molecules undergo endocytosis. Application of the bile acid taurolithocholate, a potent and specific odorant for fish, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…We stained two subsets of ciliated sensory neurons of the olfactory epithelium of crucian carp with the aid of odorant-induced uptake of fluorescent dye (Døving et al, 2011). To this end we perfused the ipsilateral olfactory epithelium, first with 10 nmol l −1 of the bile salt taurolithocholate (TLC) together with 10 µmol l −1 of a dextran conjugated with Alexa 488 in APW for 5 min, rinsed with APW for 5 min, and subsequently exposed the epithelium with 10 nmol l −1 of the alarm substance hypoxanthine-3-Noxide (H3NO) together with 10 µmol l −1 of a dextran conjugated with Alexa 647 in APW for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We stained two subsets of ciliated sensory neurons of the olfactory epithelium of crucian carp with the aid of odorant-induced uptake of fluorescent dye (Døving et al, 2011). To this end we perfused the ipsilateral olfactory epithelium, first with 10 nmol l −1 of the bile salt taurolithocholate (TLC) together with 10 µmol l −1 of a dextran conjugated with Alexa 488 in APW for 5 min, rinsed with APW for 5 min, and subsequently exposed the epithelium with 10 nmol l −1 of the alarm substance hypoxanthine-3-Noxide (H3NO) together with 10 µmol l −1 of a dextran conjugated with Alexa 647 in APW for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…H3NO is a potent odorant that evokes an alarm reaction in minnows (Brown et al, 2000), black tetra (Pfeiffer et al, 1985) and zebrafish (Mathuru et al, 2012;Parra et al, 2009). Although the odorants are different their putative role as olfactory cues in crucian carp is not yet proved, both TLC and H3NO induce activity-dependent uptake of fluorescent dye into ciliated OSNs (Døving et al, 2011). Previous studies in crucian carp have shown that the ciliated OSNs project to the medial olfactory bulb and synapse with relay neurons with axons in the medial part of the medial olfactory tract (Hamdani and Døving, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids, a feeding stimulant in fishes (Zielinski and Hara, 2006), are detected primarily by microvillous ORNs (Lipschitz and Michel, 2002;Sato and Suzuki, 2001), but also possibly by ciliated and crypt ORNs (Hansen et al, 2004;Vielma et al, 2008). In contrast, several studies demonstrated that for teleosts, bile salts are detected only by ciliated ORNs (Døving et al, 2011;Hansen et al, 2003;Sato and Suzuki, 2001). Additionally, cross-adaptation and mixture experiments confirm that teleosts possess ORs for bile salts that are independent from those for amino acids, prostaglandins, gonadal steroids and polyamines (Laberge and Hara, 2004;Michel and Derbidge, 1997;Zhang and Hara, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds, which possess diverse structures and are relatively stable in aquatic environments, are proposed to function as intraspecific chemical signals [2]. Recent studies have shown that bile acids serve as acute and specific olfactory stimuli for teleost fishes and jawless vertebrates, such as sea lampreys [3][4][5]. Since fish and other aquatic animals produce and release bile alcohols with diverse conjugations and side chains, these particular metabolites were referred to as bile acid derivates.…”
Section: Introductionmentioning
confidence: 99%